Biomarkers of manganese exposure in pregnant women and children living in an agricultural community in California - Gunier, Robert (2014)
Manganese (Mn) is an essential nutrient but at high exposure levels is a neurotoxicant. There is no wellvalidated biomarker to assess perinatal Mn exposure. A total of 75 mother-child pairs provided blood, urine, and/or deciduous tooth samples. We analyzed Mn in dentin and enamel of shed teeth; maternal, cord, and child blood; and maternal and child urine and examined the interrelationships of Mn levels in all matrices. We observed higher Mn levels in prenatal than postnatal dentin (geometric mean (GM) = 0.51 vs 0.16 Mn:Ca, p < 0.001), maternal blood at delivery than 26 weeks gestation (GM = 20.7 vs. 14.6 μg/L, p = 0.001), and cord blood than child blood at 24 months of age (39.9 vs 25.0 μg/L, p = 0.005). There were no significant correlations between Mn in dentin and Mn concentrations in maternal blood or maternal or child urine. Levels of Mn in prenatal dentin, prenatal maternal blood, and 24 month urine were higher (p < 0.05) among mothers and children living with a farm worker. Prenatal Mn levels in dentin were correlated with Mn loadings and concentrations in prenatal house dust. Levels of Mn measured in tooth dentin constitute a promising biomarker of perinatal exposure.